Aplikasi Desain Faktorial 23 pada Kadar CO2 Proses Purifikasi Bio-gas dengan Adsorben Genteng - Zeolite - Wahyudi, Slamet; Arif, Muhammad; Hidayati, Nafisah Arina (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
The CO2 content in biogas is an impurity, so it needs to be reduced. One way to reduce the levels of CO2 in biogas is by purification with tile-zeolite adsorbents. The purpose of this study was to determine the use of tile - zeolite as an adsorbent in the purification process to reduce CO2Â levels using a 23 factorial design. The use of tile powder adsorbents (25% and 75%) - Zeolite (75% and 25%), biogas flow rates of 1 and 6 liters/minute, which were investigated at intervals of 5 and 20 minutes, to collect CO2 content data. Gas Chromatography-Mass Spectrometry (GCMS) is used to test the adsorption gas content. The results are shown by the Pareto curve resulting from biogas purification of CO2 levels, each of which has a magnitude of response to CO2 levels. Increased levels of tile-zeolite as an adsorbent and the rate of biogas flow in the purification process had an effect of reducing CO2 levels by 44.214%. Conversely, an increase in tile-zeolite levels as an adsorbent increases CO2 levels in the biogas purification process. Natural tile is a porous material that can adsorb and has ions that can be exchanged with ions from the outside.